Paddy Cultivation in Kerala - Jayan Jose Thomas (Review of Agrarian Studies, 2011)
Paddy cultivation in Kerala has witnessed a steady decline since the 1980s. The sharp fall in the area under paddy cultivation as well as in the quantity of rice produced in the State has had important implications for Kerala’s economic, ecological and social development. Over the last five years, however, there have been commendable signs of a revival in rice production in Kerala. A new sense of purpose and enthusiasm is visible now among paddy cultivators in Palakkad, a region that is referred to as the “rice bowl” of Kerala. This field report, which is based partly on interviews with farmers, government officials and leaders of mass organizations in Palakkad, is an account of some of the long-term challenges facing paddy cultivation in Kerala. It also attempts to review the policy initiatives of the State and local Governments over the last few years that have helped revive rice cultivation in Kerala.